Hemoglobin Levels in the First and Third Trimesters of Pregnancy: A Comparison between Indigenous Papuan and Non-Indigenous Papuan Women - Junaiddin, Junaiddin; Etnis, Baktianita Ratna; Arianto, Muhamad Faizal; Lerebulan, Exaudian Flourens; Andirwana, Andirwana; Sulfikar, Andi; Agung, Angelich Windy R; Mulyati, Mulyati; R, Astuti (Journal of Health and Nutrition Research, 2025)
Hemoglobin (Hb) is a component of red blood cells that functions to transport oxygen throughout the body. Decreased hemoglobin levels cause anemia. The World Health Organization (WHO) recommends that ideal Hb levels are ≥11 gr/dL. Various factors such as ethnicity, environmental conditions, age, culture, parity, nutritional value, and socioeconomic status can affect the occurrence of anemia during pregnancy. The purpose of this study was to determine the comparison of Hb levels in pregnant women in the first and third trimesters, both in indigenous Papuans (OAP) and non-OAP. This type of research is quantitative analytic with a comparative research design. The population in this study were 290 pregnant women who came and underwent examinations at the Malawili Health Center. The number of pregnant women in this study was 36 people. The sampling technique used was purposive sampling. The results showed no significant difference (p > 0.05) in hemoglobin levels in pregnant women in the first and third trimesters in the OAP and Non-OAP categories. The average hemoglobin level of pregnant women in the first trimester who were anemic and not anemic was 11,076 and in the third trimester it was 10,850. The results of the study showed that the incidence of anemia was more common in pregnant women in the third trimester who did not receive iron and folic acid supplementation (non-OAP) due to lack of knowledge about the preparations needed during pregnancy. It is recommended to increase the role of health workers in providing information to pregnant women in order to reduce the incidence of anemia in pregnant women.